Sound changes in the Haloban language of the Banyak Islands, Aceh, Indonesia - Tasnim Lubis; Dwi Widayati; Amalia Amalia; Liesna Andriany; Mukramah Mukramah (Universitas Syiah Kuala, 2025)
Sound change is a universal phenomenon and is strongly influenced by contextual factors. Variant sounds that appear as cognates across languages can be identified and explained through linguistic analysis within a cultural framework. This study aims to identify sound changes in the Haloban language by comparing them with a related language spoken on Simeulue Island, the Defayan language. A qualitative method was employed in this research. Data were collected through recordings of Halobanese wordlist utterances and interviews with native Halobanese speakers. Six informants participated in the study, comprising three male and three female native speakers. Data collection involved documentation techniques, including recording, transcription, and translation into both Indonesian and English. The data were analyzed for regular and semi-regular (sporadic) sound changes between Proto-Austronesian (PAN) and Haloban. The Haloban language is spoken in only two villages in the Pulau Banyak District, Aceh Singkil Regency, Aceh Province. The results showed a regular sound change in which the PAN sound /b/ becomes /w/ in Haloban. Semi-regular changes included sound loss, addition, fusion, and unpacking. In comparison with the Defayan language, two regular sound changes were identified in Haloban: /b/ and /f/ becoming /w/. These sound changes contribute to the linguistic identity of the Halobanese people.